2011
DOI: 10.1007/bf03326213
|View full text |Cite
|
Sign up to set email alerts
|

The fate and behavior of selected endocrine disrupting chemicals in full scale wastewater and sludge treatment unit processes

Abstract: AB STRACT: Endocrine disrupting chemicals are discharged into the environment mainly through wastewater treatment processes. There is a need for better understanding of the fate of these compounds in the unit processes of treatment plant to optimise their removal. The fate of oestrone, 17β-estradiol, 17α-ethinyestradiol and nonylphenol in the unit processes of full scale wastewater treatment plants in the UK, including activated sludge plant, oxidation ditch, biofilter and rotating biological contactor were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 43 publications
(53 reference statements)
2
36
0
5
Order By: Relevance
“…These chemicals consist of synthetic and natural chemicals which affect the stability of normal hormonal functions in humans. They are mainly discharged to the environment through effluent from wastewater treatment works [1][2][3]. Several studies have shown that humans and wildlife are exposed to a combination of multiple agents of EDCs and their effects are versatile in both mammalian and non-mammalian species due to their various sources and how they are discharged to the environment [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…These chemicals consist of synthetic and natural chemicals which affect the stability of normal hormonal functions in humans. They are mainly discharged to the environment through effluent from wastewater treatment works [1][2][3]. Several studies have shown that humans and wildlife are exposed to a combination of multiple agents of EDCs and their effects are versatile in both mammalian and non-mammalian species due to their various sources and how they are discharged to the environment [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous surveys indicated that EE 2 was normally present in the lower ng/L in wastewater treatment plant (WWTP) effluents, ranging from 0.5 to 10 ng/L (Ternes et al 1999). However, the EE 2 maximum levels in domestic wastewater was 7 ng/L (Cargouet et al 2004;Ifelebuegu 2011), which meant that EE 2 could be separated from conjugated glucuronide or sulfate complexes by the function of microorganisms (Panter et al 1999). In addition, EE 2 concentration in river water ranged from below the detection limit to 4.09 ng/L with a maximum concentration of 48.8 ng/L (Chang et al 2003;Zhang et al 2011).…”
mentioning
confidence: 98%
“…Both ethinyl estradiol, a pharmaceutical with a high endocrine-disrupting ability [34], and diclofenac, identified as a contaminant that causes direct toxic effects in the environment [35,36], were found to be very sensitive to ClO 2 oxidation. However, if other less reactive…”
Section: Effluent 1)mentioning
confidence: 99%